Development and validation of Unmada symptom checklist - Suchitra S Patil; Amit Singh; R Nagarathna; H R Nagendra (Wolters Kluwer Medknow Publications, 2023)
Background: Psychosis is explained as Unmada in Ayurveda Medical Science. Types of Unmada are based on Tridosha. General and a specific symptom of Unmada have been explained in classics exclusively. Unmada is alteration in mental functions such as behavior, emotions, intellect, memory, and character. The symptoms of Unmada are (1) Mano vibhrama - altered functions of mind, (2) Buddhi vibhrama - altered discriminative power, judgment, (3) Sanjañā jñāna vibhrama - altered consciousness, (4) Smriti vibhrama - confused memory, (5) Bhakti vibhrama - altered attachment or embellishment, (6) Śīla vibhrama - altered nature or disposition, (7) Cheshta vibhrama - altered motion or gesture, and (8) Ācāra vibhrama - altered custom or practice. Many scales such as the Brief Psychiatry Rating Scale (BPRS) and positive and negative symptom scale are available from the modern perceptive. According to the Ayurveda perceptive, Unmada-specific symptom scale to measure Tridosha in psychotic patients is available, but there is a need for a standard scale to measure general symptoms so that the treatment for behavior, emotions, intellect, and memory can be planned as per the derangement. Hence, this study has been taken. Aims and Objective: The objective of the study was to develop a simple, standardized instrument to assess symptoms of Unmada according to the Ayurveda concepts in the diagnosed patients of psychosis. Methods: This was a descriptive type of study to develop a scale. A 54-item, Unmada symptom checklist (USC) was developed based on symptoms description in Ayurvedic classics and by taking the opinions of experts (five Ayurvedic experts, five psychiatrists, and five psychologists). It was evaluated in 30 patients with the diagnosis of nonaffective psychosis to check the reliability of the instrument. Moreover, the scale was administered on 30 patients who were diagnosed with psychosis. The duration for administration was about 20-25 min. Results: The reliability of a USC was good which was supported by high internal consistency values of Cronbach's α - 0.9144. Correlation between total scores of BPRS and US was 0.959 and P<0.001, which was considered as statistically significant. Interrater reliability coefficient for each item ranged from 0.627 to 0.951. Correlation, which measures of criterion related validity, was 0.950 with BPRS, which suggested that Ayurveda concepts correlate with modern concepts. Conclusions: An USC is a simple, efficient, reliable, and valid instrument for clinicians to diagnose Unmada in patients according to the Ayurveda concept. However, further research with more number of samples, more diverse groups of psychotic disorders, and a broader range of convergent and discriminant validity are needed.